Effect of filler loading of waste tire dust filled Acrylonitrile Butadiene Styrene composites - Mohamad Nurhidayat Rahmat (Universiti Malaysia Perlis, 2008)
Waste tire dust is an organic material which can be used as filler in polymer composites. Effects of filler loading of the waste tire dust filled acrylonitrile butadiene styrene composites were studied. The blend ratios of ABS to waste tire dust was fixed as 0, 5, 15, 20, and 25 phr which is the total weight are 200g per formulations. The blend was melt mixed at temperature of 1900C and rotor speed of 50 rpm. Afterwards, the blend was compression molded in an electrically heated hydraulic press and was preheat at the same temperature for about 8 minutes and cooled at room temperature. It was found that ABS/WTD composites exhibit lower mechanical properties. Tensile strength, elastic modulus was decreased while elongation at break was increased as the filler loading increased in the blends. Swelling behavior analysis show that the degree of swelling index increased as the waste tire dust content increased due to the increment of the elastomer content in the blends. The fracture surface of ABS/WTD composites is much rougher than the fracture surface of pure ABS. Many larger waste tire dust particles are distributed on the fracture surface of ABS/WTD composites. As the filler loading is increased in the ABS/WTD composites, the distribution of the WTD becomes not uniform and will cause agglomeration between the particles. The thermogravimetry analysis shows that there are two degradation steps which are associated with the elastomer in the WTD and the ABS matrix itself. Addition higher filler loading of WTD will improve thermal stability of the composites. While differential scanning calorimetry analysis shows that the glass transition temperature, Tg of the composites blend were increased with the increasing of filler loading.